A Study of the Chains of Transmission of the Hadith ‘My family is the safety of my nation...’ in Terms of the Sunni Hadith Approach - Hekmat Jarih Saber Al-Rahma ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The researcher provided insights into the transmission of the hadith Al-Aman by extracting it from its original sources, analyzing the transmission chains and reporting methods, and evaluating them based on the rules and origins of the hadith according to Sunni tradition. He determined that the hadith was reported in nine transmission chains by six companions, with no repeated narrator in the transmission chains. Otherwise, the chains of transmission of the hadith increase even more. It has become evident that some of the chains of transmission are effective on their own, while others may have minor flaws that are resolved when approached from a different angle. The hadith is reliable in every aspect without any issues. It also became evident that the alterations of the hadith by certain hadith scholars did not align with the established guidelines, and thus we observed some of them acknowledging the authenticity of the hadith.